2012
DOI: 10.1002/pits.21596
|View full text |Cite
|
Sign up to set email alerts
|

Response to intervention in mathematics: Critical elements

Abstract: While implementation efforts using a Response to Intervention (RtI) model to increase reading instruction are becoming widely used, more administrators and teachers are looking to learn effective RtI practices to support learning in mathematics. This article explores some of the key elements of RtI practices in mathematics, including screening for identification of struggling learners and progress monitoring for gauging instructional effectiveness. In addition, several of the pressing needs regarding the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 27 publications
(18 reference statements)
2
54
0
Order By: Relevance
“…Yet, there is still a need to develop an RtI system for early mathematics (Lembke et al, 2012). The findings from this study address the critical first step—assessment development—in what needs to be a sustained effort to meet that purpose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, there is still a need to develop an RtI system for early mathematics (Lembke et al, 2012). The findings from this study address the critical first step—assessment development—in what needs to be a sustained effort to meet that purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Response to Intervention (RtI)—a multi-tiered learning difficulties prevention system—is one means that has been established to provide all children with access to appropriate instruction through age- and domain-specific screening, progress monitoring, and, where necessary, targeted intervention (Fuchs & Fuchs, 2006; Lembke, Hampton, & Beyers, 2012; Vellutino, Scanlon, Small & Fanuele, 2006). The general RtI framework of screening, progress monitoring, and targeted intervention typically can be applied across domain and age-group (Riccomini & Witzel, 2010); however, specific efforts must be undertaken to design and apply age- and domain-appropriate assessments and interventions carefully.…”
Section: Early Numeracy Assessment: the Development Of The Preschool mentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend performing a universal screening in order to identify learners at risk for learning problems (Lembke et al, 2012), possibly by means of a brief experimental analysis (VanDerHeyden & Burns, 2009) or a one minute timed screening (Lin & Kubina, 2005). This will help identifying students at risk and furthermore help to pinpoint each student's level of proficiency, thus ensuring that students' receive individualized intervention at the proper level, as was the case with previous studies (Chiesa & Robertson, 2000;Gallagher, 2006).…”
Section: Recommendationsmentioning
confidence: 99%
“…Also, Binder (1996) suggested that frequencies of between 50-70 are necessary in order to maintain performance during short (two minutes) and long (four minutes or more) intervals. The PT focus upon universal screening and pinpointing also fits nicely within the Response to Intervention framework, where it is recommended that these evaluations be done three times each school year in order to identify learneras at risk for learning problems (Lembke, Hampton, & Beyers, 2012).…”
mentioning
confidence: 99%